PENURUNAN KOSENTRASI SURFACTAN PADA LIMBAH DETERGEN DENGAN PROSES PHOTOKATALITIK SINAR UV - Soraya Santi, Sintha (Jurnal Teknik Kimia, 2009)
Photokimia have used as by many alternative processing of water. Photokimia reaction is reaction of chemistry which is induction by light either trough indirect and also direct. Conversion ofr Energy light become chemical energy or electrics represent elementary principle of photokimia. To quicken reaction of conversion needed by the existence of catalis reffered as catalis system. Catalis will be active if obtaining light energy. In course of fotokimia will be formed by radical hydroxyl to degrade compound of organic underwater of waste like surfactant. The research dergradation of concentration surfactant used Titanium Dioxide catalis with light source the used is lamp of UV which variation of 15 watt, 30 watt and 36 watt. The objective of research to determine abilitry degradation of concentration of surfactant in waste of detergent. Result of research indicate that ability of degradation of be concentration use TiO2 counted 2,2 gr with result 96,5 %, time of radiating 2,5 hour and lamp energy 36 watt. Key words :Photokimia, Photokatalitik, Surfactan